OPTICAL CONTROL OF THE INTERNAL CAVITIES OF CAST ARTICLES - E. I. Marukovich; L. P. Maliavko; A. P. Markov; E. G. Shwarz (Литьë и металлургия)
The methods and means of visual control of the hard-to-reach channels of castings and moulds on the basis of light-guiding systems of the optical pictures visualization are analyzed. The constructions and technical characteristics of hard and flexible endoscopes for control of basic profilecomposite parts are given.